Comorbidity and Risk Factors for COVID-19 Confirmed Patients in Wasit Province, IRAQ - Taher, Taqi M; Sarray, Firas T; Farhan Al-Badri, Saad A; Ghazi, Hasanain Fl (AL-Kindy College Medical Journal, 2020)
Background: Coronavirus disease 2019 (COVID-19) isone of the updated challenges facing the whole world.Objective: To identify the characteristics risk factors thatpresent in humans to be more liable to get an infectionthan others.Methods: A cross-sectional study was conducted forpositively confirmed 35 patients with polymerase chainreaction in Wasit province at AL-Zahraa TeachingHospital from the period of March 13th till April 20th. Allof them full a questionnaire regarded by risk factors andother comorbidities. Data were analyzed by SPSS version23 using frequency tables and percentage. For numericaldata, the median, and interquartile range (IQR) were used.Differences between categorical groups were performed byfissure exact test.Results: The median age of the patients was 43 years oldand interquartile range (25-56 years). Majority of thepatients were female (60%) and (51%) of them were fromthe same region (AL-ezza). The dominant blood groupamong patients was (O) (40%). About 11.4% of patientshad a travel history especially to Islamic Republic of Iran,while (77.1%) had contact with positive cases. The highestpercentage of comorbidities among patients washypertension (40%), and the most presenting symptomswere cough and fever. About 51% of patients were withmild symptoms. Diabetes, coronary heart diseases, andchronic renal diseases were significantly related to diseaseseverity (P-value=0.02, 0.001, 0.01 respectively).Conclusion: Being a female, overweight or obese, andwith blood group (O) are the major risk factors amongpatients. Comorbidities can play an important role in theseverity of disease especially hypertension, diabetes,coronary heart diseases, and chronic renal diseases.